2019
DOI: 10.1074/jbc.ra118.004021
|View full text |Cite
|
Sign up to set email alerts
|

K-Ras G-domain binding with signaling lipid phosphatidylinositol (4,5)-phosphate (PIP2): membrane association, protein orientation, and function

Abstract: Edited by Henrik G. DohlmanRas genes potently drive human cancers, with mutated protooncogene GTPase KRAS4B (K-Ras4B) being the most abundant isoform. Targeted inhibition of oncogenic gene products is considered the "holy grail" of present-day cancer therapy, and recent discoveries of small-molecule KRas4B inhibitors were made thanks to a deeper understanding of the structure and dynamics of this GTPase. Because interactions with biological membranes are key for Ras function, Ras-lipid interactions have become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 109 publications
(116 reference statements)
8
48
0
Order By: Relevance
“…In particular, the HRC is enriched in PIP2 and depleted in cholesterol and polyunsaturated lipids, whereas the LRC exhibits opposite trends. These ndings on our in silico arti cial membrane corroborate RAS' preferential association with PIP2 on experimental arti cial membranes (32,33). However, discrepancy still exists between reconstituted systems and the observed enrichment of PS and phosphatidic acids in RAS nanoclusters on intact-cell PM sheets (11).…”
Section: Ras-lipid Co-localizationsupporting
confidence: 81%
“…In particular, the HRC is enriched in PIP2 and depleted in cholesterol and polyunsaturated lipids, whereas the LRC exhibits opposite trends. These ndings on our in silico arti cial membrane corroborate RAS' preferential association with PIP2 on experimental arti cial membranes (32,33). However, discrepancy still exists between reconstituted systems and the observed enrichment of PS and phosphatidic acids in RAS nanoclusters on intact-cell PM sheets (11).…”
Section: Ras-lipid Co-localizationsupporting
confidence: 81%
“…These studies have used MD simulations with the HVR attached to the lipid membrane to understand the membrane orientation of the catalytic domain of an oncogenic K-Ras (i.e. G12V-KRAS 46,47 ), but have not compared different mutant proteins or nucleotide states. Therefore, MD simulations of different membrane-bound oncogenic K-Ras proteins, as well as their comparative analyses are useful for further understanding the effects of oncogenic mutations on K-Ras dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an elegant application of NMR to K-Ras bound on lipid nanodiscs, Mazhab-Jafari MT, et al found that disease-causing RASopathy mutations such as K5N and D153V modulate the membrane orientation of K-Ras [65]. Combining MD and spectroscopic approaches, additional studies by the Sligar and Buck groups have established that membrane reorientation is modulated by the lipid composition of the host membrane [63,68]. Helix α4 and the HVR were proposed to constitute two structural elements that were used to balance the reorientation equilibrium, thus modulating the preferred orientation and probably also the ease of the reorientation [17,21].…”
Section: Activation State Dependent Orientations Of Ras On the Membranementioning
confidence: 99%